Perlindungan Hukum terhadap Hak Pegawai Negeri Sipil dalam Sistem Kepegawaian Indonesia - Paus Paus, Subaida; Markus, Dwi Pratiwi; Kirana, Anggun (Media of Law and Sharia, 2025)
Legal protection for Civil Servants in Indonesia is a crucial aspect of ensuring the professionalism and integrity of the state apparatus. The primary legal framework governing this protection is Law Number 20 of 2023 on the State Civil Apparatus, which underscores the principles of integrity, professionalism, neutrality, and freedom from political intervention within the State Civil Apparatus. Additionally, Government Regulation Number 11 of 2017 on Civil Servant Management outlines the rights and protections afforded to Civil Servants. The purpose of this research is to analyze the regulations governing legal protection for Civil Servants, identify challenges in the implementation of existing regulations, and propose recommendations to enhance policies for more effective legal protection of PNS. This study employs normative legal research methods to analyze the regulations governing legal protection, including legal assistance for Civil Servants facing legal issues related to their official duties. The findings indicate that while the legal framework provides for the rights and protection of Civil Servants, several challenges remain in its implementation. Strengthening policy enforcement and enhancing regulatory oversight are essential to ensuring effective legal protection for Civil Servants